DIALOGIC EPISTEMOLOGY IN CIRCUMSTANCES OF MODERN DEVELOPMENT OF SCIENCE - Русяєва, Т. Г. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
The paper proposes the questions related to determination of conditions which form a dialogic epistemology in circumstances of modern development of science.